(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The impact of globalization has compelled MSME sector to adopt Information and Communication Technology practices to survive and compete with large scale companies. The potential benefits of information and communication technologies (ICTs) to micro, small- and medium-sized enterprises (MSMEs) are well known. ICTs enhance MSME efficiency, reduce costs, and broaden market reach, both locally and globally. Since the MSME sector plays a major role in national economies, these benefits to individual MSMEs collectively translate into positive results in the form of job creation, revenue generation and overall country competitiveness. Governments, therefore, have an interest in the promotion of access to, and use of, ICTs by MSMEs. This study is an attempt to describe about the benefits of ICT in MSME sector and also describe that how the Ministry of MSME promotes the ICT in MSME sector through their schemes as a policy.